HUBUNGAN PENGETAHUAN, PERSEPSI DAN EFEKTIFITAS PENGGUNAAN TERAPI INSULIN TERHADAP KEPATUHAN PASIEN DM TIPE II DALAM PEMBERIAN INJEKSI INSULIN - Raphika ' Sartunus; Yesi ' Hasneli; Jumaini ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract Diabetes Mellitus (DM) is one of the most common medical problem in the world. The purpose of this descriptive correlational research on Type II Diabetic patients was to determine the relationship of knowledge, perception and effectiveness in the use of insulin therapy. This research was conducted in Arifin Achmad Regional General Hospital of Pekanbaru. Involving 78 respondents. The sampling method is purposive sample. Measuring instrument used was a questionnaire that has been tested for validity and reliability. The analysis used is univariate and bivariate. The results revealed that perception (p value = 0.000) and the effective use of insulin therapy (p value = 0.000) for patients with Type II DM compliance in the administration of insulin injection but there is no correlation between knowledge (p value = 0.211) in the delivery of insulin injection. Nurse is able to do many things in order to control the effectiveness the use of insulin on Type II DM. . Keywords: DM II, effective use of insulin therapy, knowledge, perception Bibliography: 49 (2002-2012)